Numerical and experimental investigation of dynamic deformation and destruction of a plate subjected to local loading - Bazhenov, Valentin Georgievich; Botvinkin, Anatoliy Kirillovich; Kukanov, Sergey Sergeevich; Romanov, Vladimir Igorevich; Ryabov, Alexandr Alexeevich; Skurikhin, Sergey Gennadievich (Computational Continuum Mechanics, 2008)
The numerical simulation and experimental results and their analysis are presented for the dynamic elastic-plastic deformation of a disk subjected to penetrating loading produced by a short cylindrical steel pin. The pin keeps the high level of kinetic energy due to the heavy joined mass. The computer model has been verified by the comparison of the numerical and experimental dynamic forces, and the residual displacements and deformations of the plate. The careful analysis of the deformation and failure of the plate is presented in the paper.